Living with Fate: The Lifestyle of Contemporary Astrologers. (15th February 2019) - Brady, Bernadette
Abstract : Astrologers are assumed to be a group of people whose lives are dictated by the stars. This position has been encouraged by ad hominem twentieth-century polemics where the astrologer is portrayed as a person of questionable mental ability who takes no responsibility for their life. These assumptions have been informed by the deﬁnition of fate from the Classical period of Marcus Tullius Cicero (106–43 BCE). In contrast, my research among English-speaking astrologers revealed that their lifestyle was one where beliefs about the nature of fate varied considerably from Cicero's views and that they used their beliefs in three ways: as an aid for their spiritual development, as a tool for personal reﬂection, or as a means for life-planning. The astrologers in my research actively engaged with their lives using their beliefs about fate, understanding it like a life companion rather than a life dictator.